Peran Self-Regulated Learning Sebagai Mediator Dalam Hubungan Self-Efficacy dan Prokrastinasi Akademik pada Mahasiswa - Maria Yuni Megarini Cahyono; Meilani Rohinsa; Trisa Genia C. Zega (LPPM Institut Pendidikan Nusantara Global, 2025)
To reduce academic procrastination, students need confidence in their ability to face problems and take the actions needed to complete tasks to get the expected results. Solomon and Rothblum (1984) define academic procrastination as the postponement of important academic tasks, such as preparing for exams, completing assignments, taking care of university administration and attending classes. To reduce academic procrastination, self-efficacy is needed to cope with problems and take the necessary steps to complete the task and achieve the desired results (Bandura, 1997). In their research, Klassen et al (2008) found that low self-regulatory self-efficacy predicts high academic procrastination. Individuals with low self-regulatory learning tend to procrastinate, as self-regulatory ability is an important factor affecting the emergence of procrastination behavior in students (Steel, 2007). The results of this study show that self-regulated learning has an important role that is negative, with the understanding that the large role of self-regulated learning has an impact on reducing the level of academic procrastination, and the low role of self-regulated learning has an impact on increasing academic procrastination.